2002
DOI: 10.1002/app.10277
|View full text |Cite
|
Sign up to set email alerts
|

Semicrystalline polyimide matrices for composites: Crystallization and properties

Abstract: New semicrystalline polyimide/oligoimide blends, designated for matrices in carbon fiber-reinforced composites, were developed. A specific advantage of the proposed polyimides is their ability to crystallize from the melt, therein retaining their crystallinity throughout the manufacturing process. The generation of crystallinity after melting, referred to as recrystallization, was investigated here as affected by blending the polyimides with oligoimides of a similar chemical structure. Based on thermal analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…In some cases, a nanoller can initiate the crystallization of the polymer matrix, 18,[20][21][22][23][24][25] signicantly accelerating the formation of crystallites, or even initiating their formation in the polymer under conditions which do not normally favor the crystallization, as in the case of ODPA-P3 polyimide. 26 Crystallization of a polymer matrix in a nanocomposite may signicantly impact its mechanical and thermophysical properties, which should be taken into account when developing new composite materials.…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, a nanoller can initiate the crystallization of the polymer matrix, 18,[20][21][22][23][24][25] signicantly accelerating the formation of crystallites, or even initiating their formation in the polymer under conditions which do not normally favor the crystallization, as in the case of ODPA-P3 polyimide. 26 Crystallization of a polymer matrix in a nanocomposite may signicantly impact its mechanical and thermophysical properties, which should be taken into account when developing new composite materials.…”
Section: A Introductionmentioning
confidence: 99%
“…Yudin et al 17,[23][24][25]29 investigated the crystallization initiation of the semicrystalline thermoplastic polyimide R-BAPB based on dianhydride 1,3-bis-(3 0 ,4-dicarboxyphenoxy)-benzene (dianhydride R) and 4,4 0 -bis-(4 00 -aminophenoxy)-diphenyl (diamine BAPB) in the composites with different nanollers. In particular, the authors have demonstrated that vapor grown carbon nanobers (VGCF) are twice as efficient in accelerating the crystalline formation as CNT.…”
Section: A Introductionmentioning
confidence: 99%
“…Recently, [14][15][16] we have investigated the crystallization behavior of a new semicrystalline 1,3-bis(3,3 0 ,4,4 0 -dicarboxyphenoxy)benzene (R) and 4,4 0 -bis-(4-aminophenoxy)-biphenyl (BAPB) (R-BAPB)-type PI, presented below.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of each of these factors on the ability of the PI to recrystallize and the conditions for crystallinity regeneration through the molding process of composite laminates were specified. [14][15][16] In this communication we report the preliminary results of work in progress, being a further step in the study of factors that influence the recrystallization of R-BAPB PI. It is based on the nucleating action of carbon nanotubes (CNTs) that are embedded at a very low concentration in the PI matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In a second synthesis step additional heat treatment up to 320 °C gave rise to imidized polyimide precursors. In this case at heating PI (R-Oph 2 O) from 80 to 280 °C at a chosen heating speed, a partially crystalline state was produced [9]. The degree of crystallinity as obtained from X-ray investigations was about 30-40%.…”
mentioning
confidence: 99%